ANALYSIS OF THE RELATIONSHIP BETWEEN WORK DISCIPLINE AND EMPLOYEE PERFORMANCE AT THE POPULATION CONTROL AND FAMILY PLANNING SERVICE (DPPKB) OF THE NORTH LABUHANBATU REGENCY GOVERNMENT THROUGH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Chindy Wulandari Tiur Romatua Sijabat; Abdul Rahim Matondang; Yeni Absah; Evawany Yunita Aritonang; Prihatin Lumbamraja (CV. RADJA PUBLIKA, 2025)
Employee performance is a crucial factor in determining the effectiveness of government institutions, particularly in public service agencies such as the Population Control and Family Planning Agency (DPPKB) of Labuhanbatu Utara Regency. In recent years, the agency's performance achievements have declined, allegedly due to low work discipline and weak organizational commitment among employees. This study aims to analyze the effect of work discipline on employee performance, with organizational commitment as an intervening variable. The research employs a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). Data were collected through questionnaires distributed to 57 DPPKB employees. The analysis results show that work discipline has a positive and significant effect on both employee performance and organizational commitment. Moreover, organizational commitment also significantly affects employee performance and is proven to mediate the relationship between work discipline and performance. These findings emphasize the importance of fostering discipline and strengthening organizational commitment to improve the effectiveness of public service. In conclusion, optimal improvement in employee performance can only be achieved when discipline is supported by a high level of organizational commitment.